2010
DOI: 10.4317/jced.2.e12
|View full text |Cite
|
Sign up to set email alerts
|

Some morphological features related to mandibular third molar impaction

Abstract: Objective: The aim of this study was to evaluate the effect of some morphological features of the mandible and mandibular permanent molars on impaction of mandibular third molars with panoramic measurements in a Turkish patient group. Study design: Standardized panoramic radiography variables compiled from 140 patients retrospectively were evaluated. Predictive variables included mesio-distal crown width and inclination of the mandibular molars, vertical and horizontal surface dimension between distal surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 21 publications
3
25
4
Order By: Relevance
“…The determining role of this factor has been advocated by Kaya and Tsai study in which the width of first and second molar was lesser in erupted group than the impacted group (4,17). This is consistent with the observation of the current study.…”
Section: A10supporting
confidence: 83%
See 3 more Smart Citations
“…The determining role of this factor has been advocated by Kaya and Tsai study in which the width of first and second molar was lesser in erupted group than the impacted group (4,17). This is consistent with the observation of the current study.…”
Section: A10supporting
confidence: 83%
“…2017; 12(1):e6501. (19.1 mm for females and 17.9 mm for males) in which the retromolar space was wider for females than males (17). This finding was contrary to other studies that reported larger retromolar space for males.…”
Section: A10contrasting
confidence: 56%
See 2 more Smart Citations
“…1) ranges from 16.7% to 68.6% [8]. Most studies have reported no sexual predilection in third molar impaction [9]. However, some studies found a higher frequency in females than in males [10].…”
Section: Definition and Prevalencementioning
confidence: 99%